If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 3(n + 2) Reorder the terms: 7 = 3(2 + n) 7 = (2 * 3 + n * 3) 7 = (6 + 3n) Solving 7 = 6 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 7 + -3n = 6 + 3n + -3n Combine like terms: 3n + -3n = 0 7 + -3n = 6 + 0 7 + -3n = 6 Add '-7' to each side of the equation. 7 + -7 + -3n = 6 + -7 Combine like terms: 7 + -7 = 0 0 + -3n = 6 + -7 -3n = 6 + -7 Combine like terms: 6 + -7 = -1 -3n = -1 Divide each side by '-3'. n = 0.3333333333 Simplifying n = 0.3333333333
| (3+6j)(5-j)= | | -30x+-32x=-15 | | -9y=6 | | .2x+.7=1.9 | | 2x-6=1.5+1 | | 3s^2=19s+14factor | | 112-14x=392 | | 6000=x(x-40) | | 5y+4=4y+50 | | F=2KG+2KH | | 7(5x-8)-4(8x+3)=-68 | | 2x-4-3x+30=6 | | 5y+40=5y+40 | | 4x^2-6.25=0 | | f(x)=x^2+40 | | (5x+2)(6x-10)(x+20)=180 | | 5v-8=-53 | | 200-(-400)= | | J(u-w)=t | | X^2-14x-234=0 | | 6v(4v-8)= | | 70=.28*x | | 49b^2=256 | | 3x^2+10x+8=-2 | | 4[x-5]=-3[x-5] | | 3a+12b+15= | | 9[7-(7x-9)]+6x=0 | | -2x+24=0 | | 12x+-9+62+-3x+16x+2=180 | | 4x*2=49 | | 8(x-3)+5=8x+7 | | 3(2z-6)-4(3z+1)=5-2(2+1) |